Precursory comprehension of being and problem of time in Heidegger's ontology - Meriç, Tendü. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
The subject matter of this thesis is precursory comprehension of Being which is the point of departure of Heidegger's question of Being. Heidegger brings out a new conception of time as the possibility of this comprehension. This conception is grounded in an interpretation of transcendental imagination which forms time. together with Being as the precondition of its comprehension. This study attempts to explore precursory comprehension of Being, on the basis of Dasein which is in the possession of this comprehension, in relation to time.
Keywords: Ontology.; Time.